Seers, witches and psychics on screen an analysis of women visionary characters in recent television and film - Beeler, Karin 1963- (McFarland, 2008)
"This book addresses the pervasive representation of women with unique visionary abilities in postfeminist television series and films from the 1990s to the present. These women mediate between the living and the dead or between different worlds of experience, redefining "normal" and challenging the traditional boundary between science and the inner world of visionary, mystical experience"--Provided by publisher.
"This book addresses the pervasive representation of women with unique visionary abilities in postfeminist television series and films from the 1990s to the present. These women mediate between the living and the dead or between different worlds of experience, redefining "normal" and challenging the traditional boundary between science and the inner world of visionary, mystical experience"--Provided by publisher.
Includes bibliographical references and index
Keywords: Geschichte 1990-2006; Women prophets on television; Witches on television; Women psychics on television; Fernsehprogramm; Frau; Film; Psiphänomen; Englisches Sprachgebiet